Current Account Imbalances in AsEAN Countries : Are they a Problem? - Ostry, Jonathan (IMF Working Papers; Working Paper ;, 1997)
Applying a consumption-smoothing model to five ASEAN countries reveals that excessive private consumption has not tended to characterize their widening external imbalances in recent years, except to a small degree in Indonesia and Malaysia. Beyond consumption smoothing, however, a number of factors influence the desirability of running large external deficits, including the level and composition of external liabilities, the flexibility of macroeconomic policies, and the health of banking systems. Even when the current account deficit appears sustainable, there is a case to reduce them in order to lower the risks arising from such factors.